2018
DOI: 10.3390/insects9010033
|View full text |Cite
|
Sign up to set email alerts
|

Spider Communities and Biological Control in Native Habitats Surrounding Greenhouses

Abstract: The promotion of native vegetation as a habitat for natural enemies, which could increase their abundance and fitness, is especially useful in highly simplified settings such as Mediterranean greenhouse landscapes. Spiders as generalist predators may also be involved in intra-guild predation. However, the niche complementarity provided by spiders as a group means that increased spider diversity may facilitate complementary control actions. In this study, the interactions between spiders, the two major horticul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 45 publications
2
25
0
4
Order By: Relevance
“…Therefore, such semi-natural areas are probably important to non-spider predators primarily as refuges or breeding grounds, not as foraging grounds. This finding concurs with observations by Gaigher et al (2015) and Cotes et al (2018) who reported the occurrence of parasitoids, in particular, at higher abundances and diversities in remnant vegetation surrounding agricultural field crops. Alternatively, such non-spider predators fed predominantly on crop-borne herbivore prey because these prey occur on crops at higher densities, thus easier to locate.…”
Section: Taxonomic Variation In Isotopic Signaturessupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, such semi-natural areas are probably important to non-spider predators primarily as refuges or breeding grounds, not as foraging grounds. This finding concurs with observations by Gaigher et al (2015) and Cotes et al (2018) who reported the occurrence of parasitoids, in particular, at higher abundances and diversities in remnant vegetation surrounding agricultural field crops. Alternatively, such non-spider predators fed predominantly on crop-borne herbivore prey because these prey occur on crops at higher densities, thus easier to locate.…”
Section: Taxonomic Variation In Isotopic Signaturessupporting
confidence: 93%
“…For example, Schmidt et al 2005reported enhanced spider densities within a plot containing a mixture of crop and noncrop plants; and noted that their ability to shuttle between the two habitat types may make them efficient at controlling aphid abundance across whole-field or whole-farm agricultural landscapes. Therefore, the ability of spiders to derive basal food source carbon from both crops and noncrops suggests the importance of using semi-natural field margins and hedgerows to facilitate herbivore suppression by these predators in both crop fields and semi-natural field edges (Schmidt et al 2005;Cotes et al 2018).…”
Section: Taxonomic Variation In Isotopic Signaturesmentioning
confidence: 99%
“…Conservation biological control would thus be a way to enhance the natural regulation of aphids in greenhouses. A way to promote colonization by key indigenous parasitoid species would be to provide them with habitat and food inside or outside of greenhouses (Cotes et al 2018, Rodríguez et al 2018). Indeed, impacts of landscape complexity on the natural enemies of crop pests have been widely studied (Chaplin‐Kramer et al 2011), especially for parasitoid communities (Kruess 2003, Thies et al 2003, Rand et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Management of the surrounding habitats may be a promising strategy to enhance biological control in greenhouses. Recently, methods involving the establishment of native plants around greenhouses have been studied for natural enemy conservation in a greenhouse-dominated landscape 56,57 . More importantly, these plants should increase the number of natural enemies in the surroundings and facilitate the migration of natural enemies to the greenhouses when necessary.…”
Section: Discussionmentioning
confidence: 99%